Regional Language Studies. Newfoundland, Number 02 (15 September 1969) - Butler Aldus, Judith (Memorial University of Newfoundland. Department of English Language and Literature, 1969)
Anglo-Irish dialects : a bibliography / Judith Butler Aldus.